Association between TYMS gene polymorphism and methotrexate treatment adverse drug reaction a sample of rheumatoid arthritis patients - Ali Saleh Mahdi Aljanabi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Methotrexate (MTX) is a popular therapy for MTX for several diseases, including RA, owing to its anti-inflammatory and immunomodulatory effects, but its usage is associated with adverse effects. The current study aims to study the possible relationship between thymidylate synthetase (TYMS) gene polymorphism and MTX's adverse drug reaction (ADR). The study involved 95 RA patients; Sanger sequencing polymerase chain reaction was utilized for the TYMS gene region. The MTX ADR had a high rate (88.4%); however, there was no significant association between genetic polymorphism and the incidence of overall ADR. At the same time, some haplotypes carry an increased risk of ADR, like the A657334Crs2853741Crs2606241Trs2853742haplotype, while others reduce the risk of ADR, like C657334Crs2853741Crs2606241Trs2853742haplotype, but none of the haplotypes reach statistically significant. In conclusion, there is no association between the genetic polymorphism of the TYMS gene and the development of methotrexate adverse drug reactions.